“The most seen I have ever felt”: Labour-Based Grading as a pedagogical practice of care: - Gibson, Lorena; Otsuki, Grant; Anderson, Jordan (Critical Studies in Teaching and Learning, 2023)
This paper discusses experiments with Labour-Based Grading (LBG) in undergraduate anthropology courses at Te Herenga Waka—Victoria University of Wellington. Since before the COVID-19 pandemic, we have been aware that our teaching was not serving students, especially those from different class backgrounds and historically marginalized communities, and those with learning disabilities or mental health issues. The challenges these students face are compounded by a secondary school education that does not adequately prepare them for university, leaving many feeling uncared for in the classroom. In response, we developed pedagogical practices of care using LBG. We discuss LBG as an assessment method that determines students’ grades based on the time and effort they spend on an assignment, instead of more conventional subjective criteria. We reflect on staff and student experiences with LBG to offer it as a model for a future of learning that actualizes care in the classroom.